More than dis campaign - Freddy (2016)
This paper details More Than Dis, a public communication campaign that aims to strengthen the inclusion of Persons with Disabilities (PWDs) in the workplace, in Singapore. This campaign was initiated by three final-year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University.